Intestinal-type adenocarcinoma of the Bartholin gland: A case report and literature review - Javier Martín-Vallejo; Patricia Molina-Bellido; Juan B. Laforga; Pedro A. Clemente-Pérez (Elsevier, 2021)
Purpose: To report a case of intestinal-type adenocarcinoma of the Bartholin gland treated successfully with surgery and to review the current literature. Methods: We report the case of a 45-year-old white woman with intestinal-type adenocarcinoma of the Bartholin gland treated with wide local excision followed by bilateral inguinal femoral lymph node dissection without adjuvant therapy. We also review the literature on the treatment and management of this rare tumor. We searched Pubmed / MEDLINE databases for previous case reports or series using the keywords "Bartholin gland", "adenocarcinoma" and "intestinal type". Results: We found 19 cases of intestinal-type adenocarcinoma of the Bartholin gland published up to November 2020. The treatments described varied from case to case. Conclusion: Intestinal-type adenocarcinoma of the Bartholin gland has been treated and managed in the same way as squamous carcinoma. Treatment of these cancers is understudied and involves local resection with curative intent. More case reports are needed to determine the best treatment strategies.